Role of High Resolution Ultrasonography(USG) In Ocular Pathologies - Bindu Agrawal; Ruchi Balyan; Sunil Kumar Agrawal; Suman Bhartiya (Asian Journal of Medical Radiological Research, 2020)
Background: Ultrasound is a noninvasive procedure to diagnose ocular pathologies. It can be used to differentiate ocular and extraocular diseases, to evaluate orbital trauma and to localize intraocular foreign body. It is of great help where ophthalmoscopy is impossible mainly due to opacification of transparent media. Aim & Objective: Study was to evaluate the role of USG in ocular diseases & correlate our finding with ophthalmoscopy (clinical) findings. Subjects and Methods: Study was done on 50 patients in Radiology department of Muzaffarnagar medical college, Muzaffarnagar, U.P. Examination was done using Ultrasonography (USG) machine- Philips 650 Clear vue with 5 - 12 MHz linear probe. Results: In our study ocular pathologies (includes extraocular) were most commonly seen between 6th to 7th decade (44%) with female predominance (64 %).Left eye (52%) showed slightly predominence however 14% of cases having bilateral involvement. Commonest ocular pathology was retinal detachment & cataract with equal weightage (20.5 %) followed by vitreous hemorrhage (15.3 %). Out of 11` extraocular cases, 4 were cysticercosis(36.3%) in our study. Out of 50 cases, 39 cases were diagnosed ocular pathologies & 11 cases were diagnosed extraocular pathologies. Out of them 47 were diagnosed correctly on USG while only 16 cases were diagnosed correctly by ophthalmic examination. Conclusion: USG is useful in diagnosing ocular conditions .USG had better sensitivity and specificity for both intraocular and extraocular pathologies than ophthalmoscope due to opaque media . Moreover, ultrasonography provide a cost-effective, radiation free, non-invasive technique in patients with ocular pathologies.